Laporan Kasus Penatalaksanaan Pulpitis Irreverisble Asimptomatik Gigi 24 Disertai Perforasi Lateral Berbahan MTA (Mineral Trioxide Aggregate) - Ulan Davinci Putri; Arny Try Kartinawanty (Lembaga Pengembangan Kinerja Dosen, 2025)
Background: Oral health is an important indicator of overall health, well-being, and quality of life. According to the WHO, oral health is a state of freedom from various diseases and conditions, including dental and oral diseases that limit an individual's ability to bite, chew, smile, speak, and psychosocial well-being. Therefore, it is necessary to maintain oral hygiene as an effort to improve oral health. Case report: A 45-year-old man came to Soelastri General Hospital complaining of a large cavity in his upper left tooth. The tooth had been painful for about a year and had not undergone any treatment.Extraoral examination revealed a symmetrical face. Clinical examination of the maxillary left first premolar revealed a large cavity on the distoocclusal surface with pulpal depth. Discussion: Perforations can be treated through cavity access; the prognosis depends on the elimination and prevention of infection in the perforation area and the choice of material. The success of perforation closure management is influenced by several factors, including the timing of perforation closure, the choice of material used, the location of the perforation, and adequate perforation closure. Conclusion: Case of maxillary left premolar with diagnosis of pulp necrosis which experienced lateral perforation and the area was closed using MTA, then root canal treatment.